1970
DOI: 10.3329/imcj.v3i2.4221
|View full text |Cite
|
Sign up to set email alerts
|

Gingivitis in Primary School Children of Bangladesh

Abstract: Though early diagnosis and intervention of gingivitis in school children can eliminate progression to frank periodontal diseases, no such measures in Bangladesh are in place to detect gingivitis at an early stage in school children. This survey was conducted in 2007 in the primary schools of rural, suburban and urban areas of Bangladesh to evaluate oral hygiene with special emphasis on gingivitis prevalent among 6-13 years school children. The clinical examination of the gingiva was carried out using a mouth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
0
0
1
Order By: Relevance
“…In the present study, the urban children presented with less plaque and calculus and lower PPD scores than rural children of the same age. This finding is in agreement with the results of several other studies 13 , 14 , 15 . Vadiakas et al 16 , in a similar epidemiological study, reported that adolescents living in urban dwellings had a significantly lower debris index and better periodontal health.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the urban children presented with less plaque and calculus and lower PPD scores than rural children of the same age. This finding is in agreement with the results of several other studies 13 , 14 , 15 . Vadiakas et al 16 , in a similar epidemiological study, reported that adolescents living in urban dwellings had a significantly lower debris index and better periodontal health.…”
Section: Discussionsupporting
confidence: 94%
“…Hasil penelitian ini sejalan dengan penelitian oleh Funieru et al 28 di Bucharest yang menunjukkan bahwa anak laki-laki memiliki skor gingiva yang lebih tinggi daripada anak perempuan (0,19 dan 0,18 dengan p=0,05). Menurut Mishu et al 29 yang meneliti gingivitis pada anak sekolah dasar di Bangladesh, anak laki-laki lebih banyak mengonsumsi makanan manis seperti coklat, kue, snack, dan biskuit sedangkan anak perempuan lebih patuh terhadap perintah orang tua dalam hal menjaga kebersihan gigi mulut dibandingkan anak laki-laki.…”
Section: Kejadian Gingivitis Pada Anak Sekolah Dasarunclassified